KONSTRUKSI PEREMPUAN SEBAGAI AGEN PERUBAHAN SOSIAL DAN PERTAHANAN KEMERDEKAAN INDONESIA DALAM NOVEL BURUNG-BURUNG MANYAR: KRITIK SASTRA FEMINISME PASCAKOLONIAL - Melati, Arum; Viola Yngwie; Maisyaroh Febriana Putri; Rito Panggalih; Trisna Kumala Satya Dewi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to dismantle the construction of women as agents of social change and defense of Indonesian independence in the novel Burung-Burung Manyar. This research uses qualitative type research which prioritizes data quality compared to the large amount of data. The material object of this research is Y.B. Mangunwijaya. The formal object of this research is the narrative structure in the novel Burung-Burung Manyar, the image of women in the novel, the novel's quotations, and the theory of feminism. The research data is a novel narrative system that shows research reinforcement quotes, the image of women in the novel, feminist theory and various information that is appropriate to the research topic. Data collection techniques are carried out by reading and recording the information needed in the research. The data interpretation technique was carried out by reading a series of narrative systems in the novel Burung-Burung Manyar in order to find the quotations needed to dismantle the construction of women as agents of social change and defense of Indonesian independence and then linked or analyzed using feminist theory. The results of this study are that in terms of creating and maintaining the nation, women have a sizeable contribution or contribution. This contribution is not only in the form of physical contributions but also non-physical ones. In addition, the contributions made by women are in the form of material and non-material contributions. Second, there are two factors behind women's contribution in fighting for and defending independence, namely: (1) the spirit of nationalism, (2) love of the motherland.Keywords: Women, Defense of Independence, Feminism